2001
DOI: 10.1021/ac0100188
|View full text |Cite
|
Sign up to set email alerts
|

Anodized Aluminum Wire as a Solid-Phase Microextraction Fiber

Abstract: The efficiency of anodized aluminum wire was investigated as a new fiber for solid-phase microextraction (SPME). Aluminum wires were anodized by direct current in a solution of sulfuric acid at room temperature and were conditioned at 300 degrees C for 30 min. These fibers were used for the extraction of some aliphatic alcohols, BTEX, and petroleum products from gaseous samples. The extracted analytes were transferred to a GC injector using an (inhouse-designed) SPME syringe that also allowed for an easy chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(72 citation statements)
references
References 31 publications
0
70
1
1
Order By: Relevance
“…The sampling time affects the adsorption because more water molecules can be adsorbed when given more time. Some studies have reported that a more than 10% increment in relative humidity had a negative effect on the sampling capacity of SPME coatings (13,19). Our data show that humidity increase from 20 to 40% has more effect on mass of analyte absorbed by SPME compared to high humidity.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The sampling time affects the adsorption because more water molecules can be adsorbed when given more time. Some studies have reported that a more than 10% increment in relative humidity had a negative effect on the sampling capacity of SPME coatings (13,19). Our data show that humidity increase from 20 to 40% has more effect on mass of analyte absorbed by SPME compared to high humidity.…”
Section: Discussionmentioning
confidence: 43%
“…Our data show that humidity increase from 20 to 40% has more effect on mass of analyte absorbed by SPME compared to high humidity. When humidity is low, many free sites are available on fibers and water molecules are more easily adsorbed by sampler but whenever the humidity increases under the same conditions most sites have already been occupied by water molecules and there is less tendency for further adsorption of water vapor (13,19). This result is similar to a previous study that concluded that relative humidity in range of 0 to 92% has reduced the rate of sampling of amines in air in the range of 20 to 80 percent (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods suffer from the drawbacks such as time-consumption, poor enrichment factors, and large volumes of toxic organic solvents. 7 To overcome these problems, modern analytical methods including LPME 27−30 and solid phase microextraction (SPME) 31,32 have been introduced and developed. LPME can be divided into three chief types: single-drop microextraction (SDME), 33,34 hollow-fiber-based liquid phase microextraction (HF-LPME) 35 and dispersive liquid-liquid microextraction (DLLME).…”
Section: Introductionmentioning
confidence: 99%
“…6 Several novel microextraction techniques are being developed in order to reduce the analysis step, increase the sample throughput and to improve the quality and the sensitivity of the analytical methods. The cloud point extraction (CPE), 7 the homogeneous liquid-liquid extraction (HLLE), 8,9 the liquid phase microextraction (LPME) 10,11 and the solid phase microextraction (SPME) 12,13 are fairly new methods of sample preparation. They are employed in the separation and preconcentration of environmental contaminants in different matrices and can solve some of the problems, encountered with the conventional pretreatment techniques.…”
Section: Introductionmentioning
confidence: 99%